A Improve the Activities and Learning Outcomes of Geometry Transformation Through ICARE Learning Model Assisted by Smart Apps Creator for Class IX-F Students of Jekulo 1 Middle School Semester 1 Academic Year 2022/2023 - Rodhi Rodhi (Universitas Muhammadiyah Enrekang, 2023)
This study aims to improve the activities and learning outcomes of students in class IX Jekulo Kudus1 Junior High School on geometry transformation material through a ICARE learning model assisted by smart apps creators. The subjects of this study were students of class IX-F in the 2022/2023 school year, with amounted to 30 students consisting of 14 male students and 16 female students. This research method is a classroom action research carried out in two cycles. Each cycle consists of four stages, namely planning, action, observation, and reflection. The method of data collection is done through tests, observing student learning activities and observing the implementation of teacher learning when learning takes place. The results showed that in the first cycle the percentage of students activity in the learning process was 78.33% in the active category, the average student knowledge learning outcomes was 72.50 with 76.67% classical learning mastery, the average student skills learning outcomes were 72.58 with classical learning mastery 76.77%, and teacher performance scores during learning 79.76% good category. In cycle II the percentage of students activity in the learning process was 88.34% in the very active category, the average student knowledge learning outcomes was 86.00 with 90.00% classical learning mastery, the average student skills learning outcomes was 83.17 with classical learning mastery 86.67%, and the value of the teacher's performance during learning 92.86% very good category. These results indicate an increase in activities and learning outcomes from cycle I to cycle II. Based on the results obtained, it can be concluded that the ICARE learning model assisted by Smart Apps Creator can improve student activities and learning outcomes.